N-acetyl -β-D-glucosaminidase activity in cow milk as an indicator of mastitis. Issue 2 (23rd May 2016) - Hovinen, Mari; Simojoki, Heli; Pösö, Reeta; Suolaniemi, Jenni; Kalmus, Piret; Suojala, Leena; Pyörälä, Satu
Abstract : Activity of lysosomal N -acetyl-β-d -glucosaminidase (NAGase) in milk has been used as an indicator of bovine mastitis. We studied NAGase activity of 808 milk samples from healthy quarters and quarters of cows with spontaneous subclinical and clinical mastitis. Associations between milk NAGase activity and milk somatic cell count (SCC), mastitis causing pathogen, quarter, parity, days in milk (DIM) and season were studied. In addition, the performance of NAGase activity in detecting clinical and subclinical mastitis and distinguishing infections caused by minor and major bacteria was investigated. Our results indicate that NAGase activity can be used to detect both subclinical and clinical mastitis with a high level of accuracy (0·85 and 0·99). Incomplete correlation between NAGase activity and SCC suggests that a substantial proportion of NAGase activity comes from damaged epithelial cells of the udder in addition to somatic cells. We therefore recommend determination of NAGase activity from quarter foremilk after at least six hours from the last milking using the method described. Samples should be frozen before analysis. NAGase activity should be interpreted according to DIM, at least during the first month of lactation. Based on the results of the present study, a reference value for normal milk NAGase activity of 0·1–1·04 pmoles 4-MU/min/μl for cows with ≥30 DIM (196 samples) could be proposed. We consider milk NAGase activity to be an accurate indicator of subclinical and clinical mastitis.